Knowledge management for project management: a model proposal based on a learning system - Pereira, L.; Lopes da Costa, R.; Dias, Á.; Gonçalves, R. (International Journal of Knowledge Management Studies, 2022)
Nowadays, the evolution of the organisations is more and more taken by the implementation of projects. The implementation of projects is the only way for continuous improvement and the differentiation in a market more and more global and competitive. We come across ourselves with successive failures of projects that do not fulfil its objectives; one of the main causes is the lack of shared best practices adopted in past projects. This research collects the experience of 50 certified project managers and based on this, develops one hundred scenarios of project execution using a mathematic regression analysis model and system dynamics to develop a learning model between projects in a sequence and concurrent way. The main finding is that it is possible to create an organisational knowledge base for continuous learning considering the project as the main source.